Identity Crisis and Culture of Punishment in Postmodern Society - Nedeljković, Zoran D.; Antić, Radica M. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
The paper examines the historical account of punishing individuals from the earliest civilized societies to the current postmodern era. The notion of punishment is interpreted in the paper as a moral sanction (internal and external), as well as a physical punishment, which over ages turned into torture whose purpose was punishment for punishment's sake, not moral correction of violators of custom or law, to be useful upon their return to society. The transition from torture as a religious ritual to torture, which grows into a culture of punishment, is pointed out. Punishment in conditions of war and peace has a specific dimension. War as a teacher of violence (Thucydides) in most cases takes away the meaning of punishment, which has a moral function in peacetime. But even in times of peace, punishment is relativized. Michel Foucault writes about the contemporary panopticon and the supervision of the individual in society, who is, above all, punished by the institutions of positive morality and remains without personal identity, no longer as a self-conscious individual but as a simple individual. Under the influence of biopolitical power, he is deprived of responsibility for his own existence. He is entangled in invisible threads of social roles, like a spider’s web, that he eventually stops being the bearer of. When he wants to make a moral judgment about a social relationship or a phenomenon that does not coincide with his understanding of the social world, he feels powerlessness or remorse because he cannot bear that his isolated value judgment clashes with the interests and public opinion of the dominant social group.
Keywords: morality; punishment; torture; biopolitical power; war; responsibility; law; postmodern; media